THE ESSENTIAL FACTORS OF PROFESSIONAL COMPETENCIES IN IMPLEMENTING SUSTAINABLE CONSTRUCTION - MOHAMMAD RADZI, MOHAMMAD SHAHME RIZAL (Universiti Teknologi PETRONAS, 2018)
Sustainable construction is a very important issue which is need to be addressed by the project stakeholders in the construction industry as it will be beneficial generally to the industry. By having the ambition to achieve sustainable construction, the stakeholders need to ensure they equipped themselves with the professional competencies. The purpose of this research is to find the essential factors of professional competencies to support sustainable construction. The research is conducted through survey using questionnaire, observation and interview in a group of stakeholders in a construction company named Dhaya Maju Infrastructure Asia (DMIA), a maintenance contractor and a client from Kumpulan Wang Simpanan Pekerja (KWSP) with the result of 68 respondents being achieved.